AN INVESTIGATION INTO CLIMAX RHETORICAL DEVICE (ENGLISH VERSUS VIETNAMESE) - Mai Thị Bích Hòa (Trường Đại học Ngoại ngữ, 2025)
- to identify, describe and analyze climax device in English versus Vietnamese on syntactic and pragmatic aspects. - to point out the similarities and differences in the features and ways of expressing climax device in the two languages. - to make some suggestions for the language teachers and learners.